Diurnal Variations and Driving Factors of CO2 Flux at Water–Air Interfaces in the Open-Flow Sections of Karst Underground Rivers - Danyang Li; Canfeng Li; Chao Huang; Hong Li; Xiongwei Xu; Xuefeng Peng; Guiren Chen; Liankai Zhang (Applied Sciences, 2024)
The high-intensity partial pressure of CO2 (pCO2) in karst underground rivers rapidly releases in open-flow sections. This is an important process affecting the global karst carbon cycle. This study focuses on the diurnal variation patterns and driving factors of CO2 exchange flux at the water–air interface in the open-flow sections of typical karst underground rivers in southwestern China. The inorganic carbon in water and water–air interface exchange fluxes are observed. Three representative survey stations, i.e., the outlet of the underground river (Q1), the river sections without submerged plants (H1), and the river sections with submerged plants (H2), are selected to study the CO2 exchange process and its influencing factors. The results show that the CO2 release flux at Q1 exhibits high pressure in the daytime and low pressure in the nighttime, while H1 and H2 exhibit the opposite pattern. The photosynthesis of submerged plants significantly inhibits the carbon release flux of the river, and in the river sections where submerged plants are distributed, their biological effects have inhibited approximately 0.131 Tg C/yr of carbon emissions. This study emphasizes the significant contribution of submerged plants in restraining the release of CO2, thereby promoting carbon sequestration and storage in karst water systems.